Holocaust Education (UCL Press, 2020)
Teaching and learning about the Holocaust is central to school curriculums in many parts of the world. As a field for discourse and a body of practice, it is rich, multidimensional and innovative. But the history of the Holocaust is complex and challenging, and can render teaching it a complex and daunting area of work. Drawing on landmark research into teaching practices and students’ knowledge in English secondary schools, Holocaust Education: Contemporary challenges and controversies provides important knowledge about and insights into classroom teaching and learning. It sheds light on key challenges in Holocaust education, including the impact of misconceptions and misinformation, the dilemmas of using atrocity images in the classroom, and teaching in ethnically diverse environments. Overviews of the most significant debates in Holocaust education provide wider context for the classroom evidence, and contribute to a book that will act as a guide through some of the most vexed areas of Holocaust pedagogy for teachers, teacher educators, researchers and policymakers. ; Teaching and learning about the Holocaust is central to school curriculums in many parts of the world. As a field for discourse and a body of practice, it is rich, multidimensional and innovative. But the history of the Holocaust is complex and challenging, and can render teaching it a complex and daunting area of work. Drawing on landmark research into teaching practices and students’ knowledge in English secondary schools, Holocaust Education: Contemporary challenges and controversies provides important knowledge about and insights into classroom teaching and learning. It sheds light on key challenges in Holocaust education, including the impact of misconceptions and misinformation, the dilemmas of using atrocity images in the classroom, and teaching in ethnically diverse environments. Overviews of the most significant debates in Holocaust education provide wider context for the classroom evidence, and contribute to a book that will act as a guide through some of the most vexed areas of Holocaust pedagogy for teachers, teacher educators, researchers and policymakers.